Malletia sp. - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
? Malletia sp. Fig. 7B. Material .— One specimen (ZPAL V.48/11), poorly preserved shell from the upper Paleocene of Fossildalen, Spitsbergen, Svalbard. Measurements .— ZPAL V.48/11: L, 4.7 mm; H, 3.2 mm; H/L, 0.68. Description .—Shell small, weakly inflated, elongate-ovate, inequilateral. Surface smooth without fine growth lines. Antero-dorsal margin short, sloping steeply into semicircular anterior margin; postero-dorsal margin long, nearly straight, forming bluntly pointed posterior end with broadly arcuate ventral margin. Beak not very prominent, located at anterior third of shell length. Remarks .—The investigated specimen is doubtfully classified in Malletia based on its weakly inflated shell and outline. Its outline is very similar to Malletia sp. from the Selandian (middle Paleocene) Katsuhira Formation in eastern Hokkaido, Japan (Amano and Jenkins 2017: fig. 19). However, the present species is smaller and taller than the Katsuhira species (L, 10.4–10.9 mm; H, 5.5–6.4 mm; H/L, 0.53–0.58). Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 110, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900